Nanomaterials in Animal Husbandry: Research and Prospects - Wang, Kun; Lu, Xubin; Lu, Yi; Wang, Jiacheng; Lu, Qinyue; Cao, Xiang; Yang, Yi; Yang, Zhangping (Frontiers in Genetics, 2022)
Nanomaterial anti-inflammatory, antiviral, and anticancer properties hold considerable promise for biological applications. This paper reviews the literature to explore the regulatory mechanisms and latest technology of nanomaterials in anti-inflammatory and anti-tumor applications. The review shows that nanomaterials can help to lower biological inflammation and eliminate tumors by targeting and controlling medication release. The majority of research is focused on co-assembling or coupling nanocarriers with pharmaceuticals to create therapeutic benefits by improving drug localization and release at the lesion site. Nanomaterials have advantages over similar materials and the use of nanotechnology anti-inflammatory and anti-cancer properties in animal husbandry and veterinary care is promising.